Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. The role of private associations in enhancing voluntary work in JeddahMr. Bayan Hamed Al-Harbi2. Scientific Miraculous in Holy Quran – Terminology Issue –Mr. Mohamad Mostafa Charmand3. The role of digital public relations in promoting domestic tourismSaudi Airlines Case Study for the year 2024Mr. Abdulla Hmood Almutairi, Dr. Mohammed Abdulaziz Alheizan4. The Contribution of Agricultural Activities to Rural Development in Upper Saiss and the Challenges to its Sustainability: A Case Study of the Matmata and Bouhlo Municipalities (Taza Province, Morocco) during the Period 2020-2024Ms. Fatima Ghmimed, Mr. Mohamed El-Fazziki, Dr. Jaouad El-Bazoui, Dr. Abdelouahed Bouberria5. Spatial variation of rainfall in the Medina region for the period (1985 – 2020)Ms. Najwa Mounir Al-Sahli, Dr. Fayidah Kamil Buqiri6. Social Support's Impact on Psychological Distress and Life Satisfaction among Saudi Women in Makkah CityDr. Najwa Helal Alharbi
Keywords: Journal of Human and Social Sciences